Bare and nonionic surfactant-functionalized praseodymium oxide nanoparticles: Toxicological studies. (October 2018) - Sharma, Priyanka; Kaur, Sandeep; Chaudhary, Savita; Umar, Ahmad; Kumar, Rajeev
Abstract: The applications of praseodymium oxide (Pr6 O11 ) nanomaterials in catalysis, oxygen storage materials, and optical devices are the emergent areas that possess an urgent requirement for the toxicological evaluation of these nanomaterials to determine their impact on the ecology. In the present work, we have employed a multiassay approach for the toxicological profiling of bare and nonionic surface-modulated Pr6 O11 nanoparticles (NPs). The contemporary analysis in this work has presented a great prospect to develop efficient indicators and inspect the toxic nature of bare and functionalized Pr6 O11 NPs. The effect of Pr6 O11 NPs was analyzed on germination parameters by the wheat seed germination assay and on algal growth by the paper disc approach. The influence of Pr6 O11 NPs on the percentage viability of four different types of bacteria, namely, Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Salmonella typhi, was investigated. The substantial effect of different concentrations of Pr6 O11 NPs on Allium cepa was investigated at the genomic level by using the chromosomal aberration assay. The functionalized NPs exhibited 41.05%-400% higher biocompatibility by the wheat seed germination assay and 27.1%-47.3% by the A. cepa chromosomal aberration assay than the bare NPs. In algal growth assay and antibacterial activity testing, biocompatibility of the developed functionalized NPs enhanced by 23.1%-37.1% and 10%-70.6%, respectively. The current work evaluated the toxicity of the NPs and measured the competence of the obtained data to characterize possibilities of probable threats, prominence of data requirement, and breaches that must be filled to diminish the ambiguities about the safe use of Pr6 O11 NPs. Graphical abstract: Image 1 Highlights: Facile synthesis of Pr6 O11 nanoparticles. Pr6 O11 nanoparticles display signifcant effect on wheat germination. High biocompatibility of Pr6 O11 displayed by A. cepa assay. Advaced antibacterial activity makes Pr6 O11 as potential antibacterial agents.